The Comparative Analysis of Local Public Finance Regulation in Strengthening Regional Governance - Andri Micho; Harry Nenobais; Mohamad Kusnaeni (Darul Yasin Al Sys, 2026)
Although local public finance regulation has received substantial attention within fiscal decentralization and public financial management research, comparative analyses of its institutional configuration as an integrated regulatory regime remain limited. This study aims to examine the institutional design of local public finance regulation across European countries, analyze how regulatory standards, supervisory institutions, monitoring mechanisms, and enforcement instruments interact to strengthen regional governance, and formulate policy implications for Indonesia’s fiscal decentralization reforms. A qualitative comparative government design was employed through a systematic literature review. The study analyzed documentary evidence from 21 European countries purposively selected from Local Public Finance: An International Comparative Regulatory Perspective (2021), supplemented by Eurostat Government Finance Statistics, the European Commission Fiscal Rules Database, and the OECD Tax Autonomy Database. Data were examined using qualitative content analysis involving coding, categorization, cross-country comparison, and thematic interpretation. The findings indicate that effective local public finance regulation depends not merely on the presence of numerical fiscal rules but on the institutional integration of regulatory standards, supervisory bodies, monitoring mechanisms, and enforcement arrangements within coherent governance systems. Regulatory configurations also vary according to constitutional structures, administrative traditions, and fiscal decentralization models, resulting in diverse approaches to maintaining fiscal sustainability and regional accountability. The study concludes that effective regional financial governance requires balanced institutional arrangements that combine local fiscal autonomy with robust oversight, transparency, accountability, and regulatory coordination. These findings contribute to the literature on regulatory governance, comparative government, and fiscal federalism by conceptualizing local public finance regulation as an integrated governance regime rather than a collection of isolated fiscal controls. They also provide practical implications for Indonesia by emphasizing the need to strengthen supervisory capacity, fiscal transparency, enforcement consistency, and intergovernmental regulatory coordination in local financial governance.